A comparison of patient testimonials on YouTube of the most common orthodontic treatment modalities: Braces, in-office aligners, and direct-to-consumer aligners. - Hunsaker, Riley J.; Shroff, Bhavna; Carrico, Caroline; Alford, Brennan; Lindauer, Steven J. (American Journal of Orthodontics & Dentofacial Orthopedics, 2022)
Introduction: The aims of this study were to (1) investigate and compare the educational value of the most popular YouTube (www.youtube.com; Google, San Bruno, Calif) orthodontic patient testimonials between braces, in-office aligners (IOA), and direct-to-consumer aligners (DTCA), and (2) classify the emotional response of the viewers through sentiment analysis of the video comments.Methods: Three different phrases relevant to braces, IOA, and DTCA were searched on YouTube. The 20 most popular patient testimonial videos meeting the criteria for each group were selected for a total of 60 videos. Using the YouTube application program interface for each video, 13 video metrics were extracted. An information completeness score was assigned, and the video comments were analyzed using sentiment analysis software.Results: The 60 videos included were viewed 34.4 million times by internet users. Braces videos had significantly more likes, comments, and a higher viewer interaction score than the IOA and DTCA videos. IOA videos had a higher median information completeness score than braces and DTCA videos. Of the 5149 video comments with polarity, 53.6% were positive, and 46.4% were negative (P <0.0001). There was no significant association between the treatment modality and positive or negative comments (P = 0.5679).Conclusions: There is high user engagement on YouTube with orthodontic patient testimonials. YouTube users interact with braces patient testimonials the most. YouTube viewers' comments on orthodontic patient testimonials express more positive sentiment than negative sentiment. There was no significant difference in positive and negative sentiment between the video comments for the 3 different treatment modalities.